Cationic P, O‐Coordinated Nickel(II) Catalysts for Carbonylative Polymerization of Ethylene: Unexpected Productivity via Subtle Electronic Variation. (31st May 2022) - Chen, Shi‐Yu; Ren, Bai‐Hao; Li, Shi‐Huan; Song, Yu‐Hang; Jiao, Shuang; Zou, Chen; Chen, Changle; Lu, Xiao‐Bing; Liu, Ye
Abstract: Transition‐metal‐catalyzed copolymerization of ethylene with carbon monoxide affords polyketones materials with excellent mechanical strength, photodegradability, surface and barrier properties. Unlike the widely used and rather expensive Pd catalysts, Ni‐catalyzed carbonylative polymerization is very difficult since the strong binding affinity of CO to Ni deactivates the highly electrophilic metal center easily. In this study, various cationic P, O‐coordinated Ni complexes were synthesized using the electronic modulation strategy, and the catalyst with strong electron‐donating substituents exhibits an excellent productivity of 10 4 g polymer (g Ni) −1, which represents a rare discovery that a Ni complex could operate with such exceptional efficiency in comparison with Pd catalysts. Notably, those Ni catalysts were also efficient for terpolymerization of ethylene, propylene with CO for producing commercial polyketone materials with low melting temperatures and easy processibility. Abstract : The installation of substituents with strong electron‐donating capacity on diphosphazane monoxide ligands provides a highly efficient cationic Ni catalyst. It exhibits a remarkable productivity of 31 150 g PK (g Ni) −1 for alternating copolymerization of ethylene with CO. The use of non‐noble Ni catalysts for efficient synthesis of polyketone co‐ and ter‐polymers in the industry renders this methodology extremely appealing.